Erlotinib plus either pazopanib or placebo in patients with previously treated advanced non–small cell lung cancer: A randomized, placebo‐controlled phase 2 trial with correlated serum proteomic signatures. Issue 11 (12th April 2018) - Spigel, David R.; Burris, Howard A.; Greco, F. Anthony; Shih, Kent C.; Gian, Victor G.; Lipman, Andrew J.; Daniel, Davey B.; Waterhouse, David M.; Finney, Lindsey; Heymach, John V.; Hainsworth, John D.
Abstract : BACKGROUND: This study compared the efficacy and safety of treatment with erlotinib plus pazopanib versus erlotinib plus placebo in patients with previously treated advanced non–small cell lung cancer (NSCLC). METHODS: Patients with progressive‐stage IV NSCLC after either 1 or 2 previous chemotherapy regimens were randomized to receive erlotinib (150 mg by mouth daily) with either pazopanib (600 mg by mouth daily) or placebo. During treatment, patients were evaluated every 8 weeks until disease progression or unacceptable toxicity. After a study amendment, pretreatment serum specimens for the VeriStrat assay were collected. The predictive value of the VeriStrat score (good vs poor) for progression‐free survival (PFS) and overall survival (OS) was assessed in the overall population and in each treatment group. RESULTS: One hundred ninety‐two eligible patients were randomized between February 2010 and February 2011. PFS was prolonged with erlotinib plus pazopanib versus erlotinib plus placebo (median, 2.6 vs 1.8 months; hazard ratio, 0.58; P = .001). There was no difference in the OS of the 2 groups. A good VeriStrat score predicted longer PFS and OS in the entire group and predicted longer PFS in the subgroup receiving erlotinib plus pazopanib. The addition of pazopanib increased toxicity, and this was consistent with the known toxicity profile. CONCLUSIONS: The addition of pazopanib to erlotinib in an unselected group of patients with previously treated NSCLC improved PFS and increased treatment‐related toxicity, but it had no influence on OS. The efficacy of both regimens was modest. Patients receiving erlotinib plus pazopanib had longer PFS if they had a good VeriStrat score versus a poor one. Cancer 2018;124:2355‐64 . © 2018 American Cancer Society . Abstract : A comparison of erlotinib plus pazopanib and erlotinib plus placebo in patients with previously treated advanced non–small cell lung cancer shows that the addition of pazopanib improves progression‐free survival and increases treatment‐related toxicity, but it has no influence on overall survival. The stratification of patients by the VeriStrat score shows that patients treated with erlotinib and pazopanib have longer progression‐free survival if they have a good score versus a poor one. See also pages 2272‐5, this issue.